2010
DOI: 10.1248/yakushi.130.397
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and <i>in Vitro</i>, <i>in Vivo</i> Characterization of Elastic Liposomes Encapsulating Cyclodextrin-Colchicine Complexes for Topical Delivery of Colchicine

Abstract: In the present study, an attempt was made to develop a cyclodextrin-colchicine complex and to study its eŠect on skin permeation and deposition of colchicine. Colchicine b cyclodextrin (BCD) complex was prepared by freeze-drying method and complex formation was conˆrmed by NMR and in vitro drug release study. Formulation containing cyclodextrin-drug complex showed 6-fold increase in transdermal ‰ux in comparison with drug solution. Skin retention studies were carried out with the objective of determining the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The accumulated EL (5-FU) has been observed with the slow and sustained release as depot which led to localized effect. A similar finding was observed using cyclodextrin as an enhancer to deliver hydrophilic colchicines in an EL (Singh et al, 2010).…”
Section: In Vitro Skin Permeation and Drug Deposition Studiessupporting
confidence: 83%
“…The accumulated EL (5-FU) has been observed with the slow and sustained release as depot which led to localized effect. A similar finding was observed using cyclodextrin as an enhancer to deliver hydrophilic colchicines in an EL (Singh et al, 2010).…”
Section: In Vitro Skin Permeation and Drug Deposition Studiessupporting
confidence: 83%
“…Although, EE% was improved (79.5%±1.6%), this was associated with a significant decrease in the flux (26.4±1.2 µg/cm 2 /h) and an increase in the vesicular size (152±14 nm). 12 , 13 Furthermore, no stability studies were reported for both the formulations. Stability study is important, because drug leakage from elastic liposomal vesicles commonly occurs during storage, especially when a hydrophilic drug like colchicine is incorporated.…”
Section: Introductionmentioning
confidence: 99%
“…Stability study is important, because drug leakage from elastic liposomal vesicles commonly occurs during storage, especially when a hydrophilic drug like colchicine is incorporated. 13 15 …”
Section: Introductionmentioning
confidence: 99%
“…13,59 Anti-psoriatic, anti-inflammatory, and antiacne drugs Currently, researchers have reported the management of acne, psoriasis, inflammation, and other cutaneous keratoses using colchicine, methotrexate, and tretinoin for topical delivery (Table 3). [59][60][61][62][63][64] with a desired set of goals. In brief, we have compiled limitations of these potent drugs in Table 3 that could be helpful for pharmaceutical scientists engaged in formulation design.…”
Section: Photoprotective Agentsmentioning
confidence: 99%
“…59 Table 3 summarizes some of the problems identified with MTX, tretinoin, and colchicines. [59][60][61][62][63][64][65][66] Topically delivered tretinoin was investigated for enhancing skin permeation in dermal delivery using different hydrophilic penetration enhancers such as labrasol, transcutol P, PG, and commercially available Oramix ® NS 10 (OrNS10). All of these surfactants showed increased cutaneous accumulation and transdermal delivery of the tretinoin except PG.…”
Section: Photoprotective Agentsmentioning
confidence: 99%